Fluoxetine decreases stereotypic behavior in primates - Hugo, Charmaine; Seier, Jurgen; Mdhluli, Chris; Daniels, Willie; Harvey, Brian H.; Du Toit, Don; Wolfe-Coote, Sonia; Nel, Daan; Stein, Dan J. (Progress in neuro-psychopharmacology & biological psychiatry, 2003)
Background: Primates reared in captivity may display stereotypic behaviors. These behaviors are arguably reminiscent of human obsessive–compulsive or posttraumatic symptoms, which respond to selective serotonin reuptake inhibitors (SSRIs). Captive primates with marked stereotypic behaviors were entered into a randomized controlled study of the SSRI, fluoxetine. Methods: A sample of 10 vervet monkeys with behaviors such as marked saluting, somersaulting, weaving, or head tossing was selected. Subjects were randomized to receive fluoxetine 1 mg/kg for 6 weeks ( n=5) or no treatment ( n=5). A rater blind to the medication status of subjects noted the frequency of the stereotypic behaviors. Results: Repeated-measures analysis of variance (RM-ANOVA) demonstrated a significant Group×Time difference with significantly fewer stereotypic symptoms in the fluoxetine group by endpoint. At this time, three of the five fluoxetine-treated subjects (but none of the no-treatment subjects) were responders on the Clinical Global Impressions (CGI) change item (CGI ≤2). Conclusions: Stereotypic behaviors in captive vervets gradually and partially decrease in response to administration of an SSRI, paralleling research on human anxiety symptoms. Further research on animal stereotypies may be useful in providing appropriate veterinary care, and in exploring the underlying neurobiology of certain psychiatric disorders.